(untitled) (Bangladesh Journal of Plant Taxonomy, 2008)
Nine new taxa belonging to the genera Actinodaphne Nees, Beilschmiedia Nees, Cinnamomum Schaeff. and Cryptocarya R. Br. of the family Lauraceae are described and illustrated from India and Myanmar. One new combination of the family has also been appended. Â Keywords:Â New taxa, Actinodaphne, Beilschmiedia, Cinnamomum, Cryptocarya, New combination, Potameia tirunelvelica, Lauraceae Â DOI: 10.3329/bjpt.v15i2.1739 Â Bangladesh J. Plant Taxon. 15(2): 89-106, 2008 (December) Â